De-Europeanisation or Counter-Conduct? Turkey's Democratisation and the EU. Issue 1 (2nd January 2016) - Cebeci, Münevver
Abstract: Many Turkish and European scholars have been (re)producing texts that praise the normative impact of the European Union (EU) which has helped the political transformation of Turkey. Nevertheless, the recent deterioration of democracy in the country indicates that the EU has been losing its transformative influence on Turkey. This might be regarded as de-Europeanisation. However, this article argues that the conceptual framework of de-Europeanisation can only partially explain the current situation in Turkey and the EU's impact, and that an analysis based on counter-conduct, as produced by EU governmentality, may provide insight into a subtler dynamic at work in the country.